2008
DOI: 10.1038/sj.emboj.7601966
|View full text |Cite
|
Sign up to set email alerts
|

SAGA-mediated H2B deubiquitination controls the development of neuronal connectivity in the Drosophila visual system

Abstract: Nonstop, which has previously been shown to have homology to ubiquitin proteases, is required for proper termination of axons R1–R6 in the optic lobe of the developing Drosophila eye. Herein, we establish that Nonstop actually functions as an ubiquitin protease to control the levels of ubiquitinated histone H2B in flies. We further establish that Nonstop is the functional homolog of yeast Ubp8, and can substitute for Ubp8 function in yeast cells. In yeast, Ubp8 activity requires Sgf11. We show that in Drosophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
133
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 44 publications
(79 reference statements)
3
133
1
Order By: Relevance
“…Loss of the dSAGA subunits resulted in photoreceptor axon-targeting defects indicating that the dTAF10 containing dSAGA complex plays a role in neuronal development in the optic lobe. 32 We also show that dTaf10 silencing results in increased apoptosis and wing morphology abnormalities.…”
Section: Discussionmentioning
confidence: 80%
“…Loss of the dSAGA subunits resulted in photoreceptor axon-targeting defects indicating that the dTAF10 containing dSAGA complex plays a role in neuronal development in the optic lobe. 32 We also show that dTaf10 silencing results in increased apoptosis and wing morphology abnormalities.…”
Section: Discussionmentioning
confidence: 80%
“…Ubp8 and Ubp10 are the yeast homologues of Nonstop and Scny respectively ( Table 1). 29,33 Global levels of H2Bub1 are increased to a greater extent in mutants deficient for both enzymes than either one alone, indicating non-overlapping targets of these proteases. 11,23 This is reflected in their distinct functional roles, and patterns of localization; Ubp10 is preferentially localized to silenced regions of the genome, while Ubp8 shows no such preference.…”
mentioning
confidence: 98%
“…34,35 Nonstop is the fly orthologue of yeast Ubp8, a component of the SAGA complex required for the activation of certain stressinducible genes (Table 1). 10,33 Weake et al 33 demonstrated that Nonstop may affect glial migration as part of the SAGA complex, as mutations in genes encoding other components of SAGA also disrupt axonal projections to varying extents. 33 Of considerable interest is the finding that reducing the deubiquitylation activity of SAGA in muscle results in a preferential downregulation of genes required specifically for muscle development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Increasingly, however, evidence has indicated that regulation of SAGA in multicellular organisms involves more sophisticated mechanisms than in their unicellular counterparts. 9,10 In order to gain more insight into SAGA function in multicellular eukaryotes, we turned to Drosophila. This model provided powerful genetic and biochemical tools in which to explore principles underlying SAGA-mediated gene regulation.…”
Section: 2mentioning
confidence: 99%